HIV/STIs risks between migrant MSM and local MSM: a cross-sectional comparison study in China - Jie Wu; Hong Wu; Pengsheng Li; Ciyong Lu (PeerJ, 2016)
Background. Internal migration plays a significant role in China’s HIV epidemic. However, few studies have directly compared migrant men who have sex with men (MSM) with local MSM with regard to HIV/sexually transmitted infections (STIs) risks. Methods. We conducted a study in Guangzhou, China, with the aim of understanding the differences in HIV/STIs risks between migrant MSM and local MSM. A cross-sectional study was conducted among 273 migrant MSM and 249 local MSM in Guangzhou, China. Their behavioral and serologic data on HIV/syphilis were collected and compared between the two groups. A multivariate logistic regression was used to estimate the associations between HIV/STIs risks and migratory status. Results. Migrant MSM, compared to local MSM, have higher odds of reporting unprotected anal intercourse (UAI) (OR = 1.4; 95% CI [0.9–2.0]) and having multiple homosexual partners (OR = 1.2; 95% CI [0.8–1.8]). A lower rate of condom use at homosexual debut was reported in migrant MSM than in local MSM (OR = 0.7; 95% CI [0.5–0.9]). Migrant MSM have less odds of reporting HIV/STIs testing in the previous 6 months relative to local MSM (OR = 0.5; 95% CI [0.4–0.8]). In addition, migrant MSM demonstrated a lower level of HIV knowledge than local MSM (OR = 0.4; 95% CI [0.2–0.8]). Conclusion. Migrant MSM are more likely to engage in sexual risk behaviors, report a lower level of HIV knowledge and have less access to HIV/STIs testing. Further comprehensive interventions targeting migrant MSM are urged.